Occupational Safety and Organizational Commitment of personnel in the hotel sector, city of Lima- Peru, in the period of 2017 - Sánchez Antezana, Karen Samantha (2022)
The hotel sector has a potential set of occupational risks inherent to the activity, which can be generated by the actions of the same job, by the distraction and behavior of the worker or the inadequate conditions to perform their functions; For this reason, the general objective was to determine the relation that exists between Occupational Safety and Organizational Commitment of personnel in the hotel sector, city of Lima- Peru, 2017. Methodologically, it was a descriptive method, correlational level, non-experimental design: descriptive -correlational. The variables are: Occupational Safety and Organizational Commitment. The population was made up of the staff of the hotel companies Monteluna S.A.C. and Inversiones PIMI S.A.C. The sample size was determined by applying the relevant statistical formula, and the sample selection was made through stratified probability sampling and simple random sampling. The survey was used as techniques and the questionnaire as an instrument. As data processing techniques, descriptive statistics, and inferential statistics (Spearman's Rho) were used to test the hypotheses, obtaining a value of 0.981 for Spearman's Rho and 0.00 in significance, proving that there is a direct and significant relationship between Occupational Safety and Organizational Commitment.